Pengungkapan dan Penerapan Etika Bisnis terhadap Kinerja Keuangan dengan Reputasi Auditor Sebagai Moderasi (Studi Empiris pada Perusahaan Manufaktur Periode 2017-2020) - Rahma Jariatul Hajah Rizka; Annita Mahmudah; Agustinus Salukh (Departement of Mathematics Education, 2022)
This study aims to examine and analyze the effect of Disclosure and Application of Business Ethics on Financial Performance with Auditor Reputation as Moderation. This study uses quantitative methods. The population used in this study uses manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020 by using a sampling technique, namely purposive sampling as many as 452 samples based on specified criteria. The variables studied in this study are Disclosure and Application of Business Ethics which are independent variables, Financial Performance as the dependent variable and Auditor's Reputation as the moderating variable. The research data were analyzed using Moderated Regression Analysis (MRA) using SPSS Version 26 analysis tool.The results of the study show that 1) Disclosure of Business Ethics has a negative effect on financial performance, 2) The application of Business Ethics has a positive effect on financial performance, 3) The reputation of the auditor is not able to strengthen the influence of the disclosure of business ethics on financial performance, 4) The reputation of the auditor is not able to strengthen the influence of the implementation business ethics on financial performance.